Development of Make a Match Card Application Learning Media on Learning Outcomes in The Topic Growth and Economic Development - Henny Tamara Pattipeiluhu (Universitas Sebelas Maret, 2020)
The COVID-19 outbreak has caused the government to require students to learn from home, but the facilities owned by schools to support the online learning process are very minimal, therefore researchers are innovating to develop a computer-based learning media in economic learning in high schools called Make A Match Card which can be done online and aims to improve student learning outcomes. The 4 stages of define, design, develop, and dissaminate are the stages of the 4D model from Thiagarajan and co. used in this study. The data collection technique was done in 2 ways, namely pretest using google form and posttest using Make A Match Card media. Data collection was carried out in class XI IIS 1 SMA Negeri 8 Surabaya. Learning outcomes obtained before the application of the media, 35% of students obtained scores above the Minimum Completeness Criteria (KKM), but after the media was applied it increased by 53% to 88% of students who obtained scores above the Minimum Completeness Criteria (KKM).